Advances in Manufacturing II Volume 2 - Production Engineering and Management - Hamrol, Adam; Kujawińska, Agnieszka; Barraza, Manuel Francisco Suarez (Lecture Notes in Mechanical Engineering,, 2019)
This book covers a variety of topics in manufacturing, with a special emphasis on product design, production planning, and implementation of both resources and production processes. The content is based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held in Poznan, Poland on May 19-22, 2019. The main focus is on showing best practices to use tools currently available in the enterprises to effectively improving industrial processes. Knowledge and production flow management, decision-making systems, production leveling, enterprise efficiency, as well as maintenance, modeling and simulation of production processes are just some of the topics discussed in this book, which offers a timely and practice-oriented reference guide for applied researchers, product engineers and product managers.